Discussion on Geraghty Type Hybrid Contractions. (6th November 2020) - Alzaid, Sara Salem; Fulga, Andreea; Alshammari, Fehaid Salem
Abstract : In this manuscript, we define the notion of Geraghty type hybrid contractions in the setting of b -metric spaces. We prove the existence of a fixed point for such mappings whenever b -metric space is complete. Our observed results not only unify several existing results but also extend some known results.